Neotypification of Protoparmeliopsis garovaglii and molecular evidence of its occurrence in Poland and South America - Katarzyna Szczepańska; Pamela Rodriguez-Flakus; Jacek Urbaniak; Lucyna Śliwa (MycoKeys, 2019)
Protoparmeliopsis garovaglii is a widely distributed placodioid lichen, which develops a distinctly rosette thallus, composed of elongated and strongly inflated to sinuous-plicate lobes. The taxon is characterised by high morphological plasticity and varied composition of secondary metabolites. However, the epithet was never typified. As such, the identity of P. garovaglii, in its strict sense, was unknown for a long time. Our phylogenetic ITS rDNA analyses, including newly generated sequences, show that European (Austria, Poland), North American (USA) and South American (Bolivia, Peru) specimens of P. garovaglii are placed in a strongly supported monophyletic clade, sister to P. muralis. We provide the first molecular evidence of the occurrence of P. garovaglii in South America (Bolivia and Peru) and the second record in Central Europe (Poland) was also provided. Furthermore, we neotypify P. garovaglii and it is reported here for the first time from Poland.